Novel palladium-guanine-reduced graphene oxide nanocomposite as efficient electrocatalyst for methanol oxidation reaction. (April 2019) - Ng, Jen Chao; Tan, Chou Yong; Ong, Boon Hoong; Matsuda, Atsunori; Basirun, Wan Jefrey; Tan, Wai Kian; Singh, Ramesh; Yap, Boon Kar
Graphical abstract: Highlights: Guanine is a nucleobase found in deoxyribonucleic acid and ribonucleic acid. Guanine was noncovalently functionalized onto the surface of reduced graphene oxide. Guanine controlled the shapes of the palladium nanoparticles. Guanine exhibits catalytic activity towards methanol oxidation reaction. The amino, imino, and amide groups of guanine act as anchoring sites of palladium nanoparticles. Abstract: The agglomeration of metal catalysts can limit the performance of fuel cells. Herein, an easy, scalable, one-pot microwave-assisted method is proposed to introduce guanine, which is a nucleobase found in deoxyribonucleic acid and ribonucleic acid, to the reduced graphene oxide-supported palladium via noncovalent functionalization. Considering the abundant amino, amide, and imino functional groups of guanine that act as anchoring sites, palladium nanoparticles of various shapes such as triangular, rectangular, circular, and diamond are uniformly distributed. The guanine itself is revealed to be catalytically active toward methanol oxidation reaction, serving as second catalyst. Consequently, the as-produced nanocomposite has a larger electrochemically active surface area (111.98 m 2  g −1 vs. 63.80 m 2  g −1 ), greater methanol electro-oxidation ability (1017.42 mA mg −1 vs. 359.80 mA mg −1 ), and higher stability in alkaline medium than its counterpart without guanine.